REQUIREMENTS ENGINEERING MODEL FOR SELF-ADAPTIVE SYSTEMS DEVELOPMENT IN HANDLING UNCERTAINTY OF CONTEXTUAL REQUIREMENTS - Aradea
The environmental complexity of a system has created a challenge for software developers. Changes can happen quickly, unexpectedly and continuously. So, software systems is required to have the ability to understand and act on what is happening within the system itself and the environment. Self-adaptive systems are the solution to these challenges, but the issue of uncertainty is still the main concern of today's researchers. Descriptions of requirements prepared during design-time may not be applicable at run-time in the event of unforeseen circumstances, so that the requirements engineering activity does not adequately capture the knowledge and construct it in accordance with systems-as-is. However, knowledge for systemsto-be is a requirement that must be met. In other words, requirements engineering should be able to bridge and align requirements at the design-time and run-time. In addition, another important factor is the fulfillment of user preferences that can be considered as part of the overall system adaptability.